Analysis of Global Warming Potential (GWP) in Waste Transportation System Using Life Cycle Assessment Method in Panakkukang District, Makassar City - Wahyudi, Didy; Chaerul, Muhammad; Marzuki, Ismail (ASTONJADRO, 2025)
Global warming is an ecosystem imbalance caused by an increase in atmospheric temperature mainly caused by the Greenhouse Gas effect. Global warming potential (GWP) is caused by several human activities, one of which is waste management. This study aims to analyze the environmental impact, especially on the amount of GWP in the waste transportation system in Panakkukang sub-district, Makassar using the Life Cycle Assessment method of Simapro software version 9.5. The research stages by analyzing the transportation route that has been applied and then comparing it with the scenario route as an alternative route on the type of arm roll truck vehicle. The research shows in general that the existing route is the shortest transportation route with the smallest GWP impact. The amount of GWP for the entire waste transportation route in the Panakkukang sub-district, Makassar is 1,352, 64 kg CO2 eq.